Entrevista al Dr. Eduardo Ibarguen Mondragon - Chaves, Andres; Ibarguen Mondragon, Eduardo (Revista SIGMA, 2016)
Abstract. Ideas and experiences of professor Eduardo Ibarguen related with investigation on mathematics are presented. Also it talks about current research projects in which He intervenes and prospects for your area at the University of Nariño. Resumen. Se presentan ideas y experiencias del profesor Eduardo Ibarguen en torno a la investigacion en matematicas, tambien se aborda acerca de los proyectos de investigacion en los cuales el interviene y las perspectivas para su area de investigacion en la Universidad de Nariño.